Environmental education and interdisciplinarity as boosters environmental management - Nunes, Denise Silva; Carvalho, Cibelle Machado (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper aims to analyze the 'interdisciplinary' environmental education and environmental management as boosters. The research problem is the lack of awareness on the implementation of environmental management awarded interdisciplinarity, which will allow better results, whether in business or public administration framework. Environmental issues fall within an interdisciplinary perspective and thereby promote management with planning and sustainable use of resources implies adding a knowledge policy that promotes the articulation of science and the integration of knowledge. In this sense, there is interdisciplinarity, as an integration of knowledge and citizenship policy, to be aggregated in environmental management in order to reformulate strategies to new environmental rationality directed toward sustainability. The methodology used in this study was descriptive and deductive method approach, using the technique of literature, the analysis of scientific, journals articles, query legislation, books and magazines. As a final result, it is emphasized that the environmental management needs of social participation in the management of environmental issues. Through environmental education and interdisciplinarity, while strategies citizenship can enhance environmental management.